A phenomenological analysis of the experience of analogical thinking in graphic design elaborations / Mohd Hafnidzam Adzmi, Zahari Ishak and Che Aleha Ladin - Adzmi, Mohd Hafnidzam; Ishak, Zahari; Ladin, Che Aleha (Universiti Teknologi MARA, 2022)
Analogical thinking is one of the thinking processes that is associated with creativity. This paper explores how it is experienced in Graphic Design elaborations using Computer Graphic Technology (CGT). Data are collected through concurrent and retrospective probing from three undergraduates and analysed through phenomenological reduction to identify the constituents and elements of the creative analogy's general psychological structure. The findings show that the general structure of the creative analogical experience is a relationship between three constituents namely 1) the experience of recalling knowledge or information, 2) the use of knowledge for ideation and 3) the use of knowledge to conclude ideas. The findings also show that the underlying elements of these constituents are conceptual(declarative) and technical(procedural) knowledge and its combinations that are consistent with the theories of analogical thinking. This article concludes with recommendations for future research and insights on its implementation in Design Education.